Interim Report on Evaluation of Consumer Cooperatives - Planning Commission (Planning Commission, 1965)
In pursuance of a recommendation of the 1964 Conference of Registrars of Cooperative Societies, the Ministry of Community Development and Cooperation (Department of Cooperation) approached the Programme Evaluation Organization for an evaluation of the organization and functioning of the consumers cooperatives set up under the relevant centrally sponsored scheme. The P.3.0, accepted the assignment and initiated the study towards the end of 1964, after finalizing, in consultation with the Department of Cooperation, the objective and scope of the enquiry. In view of the short period for which the scheme has been in operation, no end-evaluation of these cooperatives has been attempted.
Programme Evaluation Organisation Planning Commission Government of India